Revealing the role of school principals in Palestine in activating the school activities and its relation in raising the level of students' achievement - Salha, Mohammad Omran; Harfoush, Yousef Fahmi; Harfoush, Nour Waleed (Journal of Educational and Psychological Sciences, 2021)
The present study aimed at revealing the role of school principals in Palestine in activating the school activities and its relation in raising the level of students' achievement from the teachers’ point of view of the higher elementary stage. To achieve the objective of the study, a questionnaire was developed consisting of (34) paragraphs divided into five areas: cultural and artistic activity, scientific activity, social activity, scout activity, sports activity, and verified its validity and stability, and then distributed to the study sample consisting of (180) teachers, who were chosen in a simple random way, and used descriptive approach in this study, and the results showed the role of school principals in Palestine in activating school activities from the teachers’ point of view came at a high level, The mean of the instrument as a whole was (3.88) The results of the study also showed that there were no statistically significant differences between the average scores of the respondents on the total score, due to the variables of the study (gender, experience, qualification, and specialization). The results also showed a statistically significant positive correlation between the degree of student activity from the teachers’ point of view and the achievement of their students in the primary stage.In the light of the study, Findings the researcher recommended a number of recommendations, including: motivating teachers who work with the student activities for the positive results of the study, and involve the community institutions in student activities.
Keywords: The role of school principals; student activities; upper elementary stage; Ramallah and al-Bireh governorate